Presentation a Model for the Maturity of Knowledge Management in the country's physical education agencies. - Lida Dehghani; Mahvash Nourbakhsh; Parivash Nourbakhsh; Mehdi Kohandel (Research in Sport Management and Marketing)
Purpose: Design a model maturity for KM in the education ministry of with a holistic approach. Method: It Is Mix exploratory that the statistical community of that, the professors and experts in the field of KM. In the assessment stage, experts in charge of physical education department. Sample volume in the first stage, 65 articles, through the revision process, in the second step from judgmental sampling to theoretical saturation and in the third stage based on Morgan chart, is a population of 278, which was used to choose the statistical population from the stratified random sampling method. The data collection tool in Meta synthesis using Shannon's entropy, to determine the validity of Glynn's critical evaluation. In the survey stage, three questionnaires were used with the reliability of the first, second and third, respectively, α=0.91, α=0.9 and α=0.9. In the evaluation stage, the questionnaire was used to assess the maturity of the KM (Researcher-made), whose reliability was calculated α=0.9. Results: All categories, concepts and maturity codes extracted from qualitative method are considered suitable for experts and can be considered as dimensions of the organizational KM maturity model and they can be developed as dimensions of the organizational KM maturity model. In terms of the level of the codes, concepts and categories are at the level of commitment (level 2), and the percentage of organizational KM maturity is 58.7 %. Conclusion: The stage show will enable the organization to assess its current position and develop appropriate plans to reach higher levels .